2021
DOI: 10.3390/sports9090117
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Testing and Game Performance in Ice Hockey: A Scoping Review

Abstract: Background: Despite the exhaustive body of literature on the demands of ice hockey, less is known about the relationships between functional performance testing protocols (on ice and off ice) and performance in a game situation. The objective of this review is to provide an overview of these associations. Methods: This review aims to identify on- and off-ice testing currently used in the scientific literature and their possible transfer to game performance as well as identifying research gaps in this field. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
(197 reference statements)
0
6
0
Order By: Relevance
“…Some interesting examples prevail in emerging approaches such as post-activation potentiation (Lagrange et al, 2020) and resistance training with focus on eccentric contraction time (Gepfert et al, 2021), which showed benefits among elite hockey players. However, despite the potential of such methods, the benefits to game specific performance remain to be shown empirically with objective game-performance measures (Huard Pelletier et al, 2021).…”
Section: Summary Of Results Limitations and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some interesting examples prevail in emerging approaches such as post-activation potentiation (Lagrange et al, 2020) and resistance training with focus on eccentric contraction time (Gepfert et al, 2021), which showed benefits among elite hockey players. However, despite the potential of such methods, the benefits to game specific performance remain to be shown empirically with objective game-performance measures (Huard Pelletier et al, 2021).…”
Section: Summary Of Results Limitations and Future Perspectivesmentioning
confidence: 99%
“…Indeed, it is important to identify attributes that are closely linked to a corresponding dimension observed in match situations. In this regard, Huard Pelletier et al (2021) showed that the relationships between functional performance and game were inconclusive and the choice of indicators combined with modern technology for in-game data collection might be a way to fill this research gap.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, systematic reviews focused on longitudinal off-ice fitness, physiological parameters and on-ice evaluation ( 40 ) as well as on-ice performance testing with an emphasis on straight sprint acceleration and speed ( 41 ). Nevertheless, many challenges remain when researchers attempt to establish associations between attributes tested on the ice and how these attributes translate into real performance in competition settings ( 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…Through the developmental model for sports such as ice hockey, organizations and coaches are interested in knowing more about the determinants of performance contributing to success, to propose adapted content [ 12 ]. With this long-term developmental approach in mind, talent identification processes have been developed [ 13 , 14 ], based on the assessment of anthropometric characteristics (e.g., body mass, height, body mass index); body composition (i.e., body fat percentage, lean mass rate) [ 15 , 16 ]; as well as performance, specifically, power–strength–velocity performances in jumping, sprinting and/or skating, and throwing/throwing [ 17 , 18 ]. Therefore, the stakeholders involved in team selection (and player evaluation) processes rely on all or on part of these precise, comprehensive, and complex evaluation methods [ 19 , 20 ], while considering the modern evolution of the sport and the associated standards [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The systematic review by Huard-Pelletier and colleagues provides us with an overview of the relationships between the different aspects of performance mentioned above. The relationships between physical fitness tests and on-ice performance (skating and match) are relatively well established and accepted [ 13 ], whether at the professional or youth level. In team sports, interactions exist between anthropometry, performance, and selection of adolescent athletes [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%